From Localization to Glocalization: Contriving Korean Pop Culture to Meet Glocal Demands - Oh, Ingyu (Archīum Ateneo, 2024)
Hallyu (the Korean Wave) has been around the world since the late 1990s. Over the period of twenty years, Hallyu has evolved from a regional entertainment pop to a global cultural content. The evolution of Hallyu, like any other evolutions, has involved a long process of localization and globalization. Both K-pop and K-dramas, the two major pillars of the Hallyu revolution, are foreign imports. K-pop has mostly been influenced by European and American dance music since the early 1990s, whereas K-dramas have been heavily influenced by Japanese trendy TV dramas in the past, particularly during the 1980s. However, the localization of K-pop and K-dramas by Korean artists, writers, and producers demonstrated their adept rearrangement skills that ushered in a new era of a domestic pop culture boom that had been on the verge of destruction due to Hollywood films, Japanese pop culture contents, and the financial crisis that swept through the nation since 1997. K-pop and K-dramas have successfully gained domestic fame to propagate its commercial influence in Asia, Europe, Latin America, and North America. The collection of papers gathered in this Forum Kritika on Hallyu Studies presents their analyses on the process of localizing and globalizing Hallyu, or what I call glocalization. Briefly, glocalization denotes a successful localization of foreign products so much so that original inventors of the products want to import the local variations instead of their originals. Americans buying a massive number of Japanese cars, for example, is a good case of glocalizaiton. Hallyu’s glocalization success indicates that the domestic Korean demand for high quality pop culture has induced new types of competition that required importing global pop content, simultaneously requiring them to contrive to produce better quality pop content than the originals for re-exporting to foreign markets, given the enormous investments that cannot be recouped from a small Korean market.